Projected impacts of climate change and anthropogenic effects on habitat distribution of endangered Javan Hawk-Eagle in Indonesia - Syartinilia; Aryo Adhi Condro; Satoshi Tsuyuki (Geography and Sustainability, 2024)
Changing climate will jeopardize biodiversity, particularly the geographic distribution of endemic species. One such species is the Javan Hawk-Eagle (JHE, Nisaetus bartelsi), a charismatic raptor found only on Java Island, Indonesia. Thus, it is crucial to develop an appropriate conservation strategy to preserve the species. Ecological niche modeling is considered a valuable tool for designing conservation plans for the JHE. We provide an ecological niche modeling approach and transfer its model to future climate scenarios for the JHE. We utilize various machine learning algorithms under sustainability and business-as-usual (BAU) scenarios for 2050. Additionally, we investigate the conservation vulnerability of the JHE, capturing multifaceted pressures on the species from climate dissimilarities and human disturbance variables. Our study reveals that the ensemble model performs exceptionally well, with temperature emerging as the most critical factor affecting the JHE distribution. This finding indicates that climate change will have a significant impact on the JHE species. Our results suggest that the JHE distribution will likely decrease by 28.41% and 40.16% from the current JHE distribution under sustainability and BAU scenarios, respectively. Furthermore, our study reveals high-potential refugia for future JHE, covering 7,596 km2 (61%) under the sustainability scenario and only 4,403 km2 (35%) under the BAU scenario. Therefore, effective management and planning, including habitat restoration, refugia preservation, habitat connectivity, and local community inclusivity, should be well-managed to achieve JHE conservation targets.